Potentiation of the bronchoprotective effects of vasoactive intestinal peptide, isoprenaline, and theophylline against histamine challenge in anaesthetised guinea pigs by adrenomedullin. - Kanazawa, H. (1996)
BACKGROUND: Adrenomedullin is a hypotensive peptide recently discovered in human phaeochromocytoma which has been found to inhibit bronchoconstriction induced by histamine and acetylcholine. This study was designed to determine the manner in which adrenomedullin and other bronchodilators interact in modulating airway function. METHODS: A study was undertaken to determine whether adrenomedullin potentiated the bronchoprotective effects of isoprenaline, vasoactive intestinal peptide (VIP), and theophylline against histamine-induced bronchoconstriction in anaesthetised guinea pigs in vivo. RESULTS: Adrenomedullin in a concentration of 10(-9) M significantly inhibited histamine-induced bronchoconstriction but in a concentration of 10(-10) M it did not exhibit the bronchoprotective effect against histamine. VIP (10(-9) M) did not affect histamine-induced bronchoconstriction but it markedly inhibited the bronchoprotective effect against histamine in the presence of adrenomedullin (10(-10) M). VIP (10(-6) M) significantly inhibited histamine-induced bronchoconstriction but this effect was short lived. Adrenomedullin in a concentration of 10(-10) M potentiated bronchoprotection induced by VIP (10(-6) M) and prolonged it. Isoprenaline (10(-8) M) also significantly inhibited histamine-induced bronchoconstriction and this effect was enhanced in the presence of adrenomedullin (10(-10) M). Similarly, adrenomedullin (10(-10) M) significantly potentiated theophylline-induced bronchoprotection, and a sub-bronchoprotective dose of theophylline (20 mg/kg i.p.) was effective in preventing histamine-induced bronchoconstriction in the presence of adrenomedullin (10(-10) M). CONCLUSIONS: This study shows that adrenomedullin potentiates the bronchoprotective effects of different classes of bronchodilators against histamine challenge in anaesthetised guinea pigs.